Ordboksprosjektet NORDLEXIN-N - Bjørneset, Tove (LexicoNordica, 1999)
A project team at the HIT centre, University of Bergen, has since 1996 been working on transferring the source material of the Swedish dictionary series LEXIN to Norwegian. The LEXIN dictionaries are customized for non-native speakers who have limited proficiency in the source language and who may also be unfamiliar with the use of dictionaries as such. The Swedish source material amounts to approx. 30.000 entries distributed on the quantitative selections MINI (approx. 5.000 entries), MIDI (approx. 8.000 entries), STORA (approx. 17.000 entries), and MAXI (approx. 30.000 entries). The objective of the project is to exploit as much of the Swedish source material as possible in order to develop a similar Norwegian database. This may in turn be linked to the already existing translations (approx. 20 languages), so that a similar dictionary series can be automatically generated in Norway. This article gives a short outline of the work carried out so far.